Pengaruh Kompetensi Kepribadian Guru PAK Terhadap Motivasi Belajar Siswa Kelas XI SMA Negeri 1 Sipoholon Kabupaten Tapanuli Utara Tahun Ajaran 2023/2024 - Yosia MF. Simanjuntak; Tianggur Medi Napitupulu; Dorlan Naibaho (Jurnal Pendidikan Agama dan Teologi, 2024)
The aim of this research is to determine the positive and significant influence of the Personality Competencies of Religious Education Teachers on the Learning Motivation of Class The research method used is a quantitative method. The population is all Class Data was collected using a positive closed questionnaire with 57 items, namely 35 items for variable Academic Year 2023/2024, proven through the following data analysis: 1) Test analysis requirements: